St. Andrews Church (Church : Brunswick County, Va.) memorandum - St. Andrews (Church : Brunswick County, Va.)
Fair copy of a memorandum of the vestry of St. Andrews parish recommending that the Rev. George Purdie be retained as rector. Signed by Thomas Stith.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Purdie, George; Stith, Thomas; Church of England -- Virginia -- History -- 18th century; Brunswick County (Va.) -- History; Virginia -- Church history -- 18th century